Genomic Diversity of Enterotoxigenic Strains of Bacteroides fragilis. - Jessica V Pierce; Harris D Bernstein (PLoS ONE, 2016)
Enterotoxigenic (ETBF) strains of Bacteroides fragilis are the subset of strains that secrete a toxin called fragilysin (Bft). Although ETBF strains are known to cause diarrheal disease and have recently been associated with colorectal cancer, they have not been well characterized. By sequencing the complete genome of four ETBF strains, we found that these strains exhibit considerable variation at the genomic level. Only a small number of genes that are located primarily in the Bft pathogenicity island (BFT PAI) and the flanking CTn86 conjugative transposon are conserved in all four strains and a fifth strain whose genome was previously sequenced. Interestingly, phylogenetic analysis strongly suggests that the BFT PAI was acquired by non-toxigenic (NTBF) strains multiple times during the course of evolution. At the phenotypic level, we found that the ETBF strains were less fit than the NTBF strain NCTC 9343 and were susceptible to a growth-inhibitory protein that it produces. The ETBF strains also showed a greater tendency to form biofilms, which may promote tumor formation, than NTBF strains. Although the genomic diversity of ETBF strains raises the possibility that they vary in their pathogenicity, our experimental results also suggest that they share common properties that are conferred by different combinations of non-universal genetic elements.